2019
DOI: 10.1016/j.ijfoodmicro.2019.108331
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific hybridisation among diverse Saccharomyces species: A combined biotechnological solution for low-temperature and nitrogen-limited wine fermentations

Abstract: Lack of the prezygotic barrier in the Saccharomyces genus facilitates the construction of artificial interspecific hybrids among different Saccharomyces species. Hybrids that maintain the interesting features of parental strains have been applied in industry for many beneficial purposes. Two of the most important problems faced by wine makers is nitrogen deficiency in grape must and low-temperature fermentation. In our study, hybrids were constructed by using selected low nitrogen-demanding cryotolerant S. eub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…This difference could be explained by a significant direct incorporation into proteins of their counterparts taken from the medium. Indeed, the inability of the two NS species to use histidine to support growth has been previously demonstrated [ 25 ]. This work also reported that T. delbrueckii displayed reduced fermentative activity when lysine was provided as the sole nitrogen source, while M. pulcherrima was simply unable to grow under these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference could be explained by a significant direct incorporation into proteins of their counterparts taken from the medium. Indeed, the inability of the two NS species to use histidine to support growth has been previously demonstrated [ 25 ]. This work also reported that T. delbrueckii displayed reduced fermentative activity when lysine was provided as the sole nitrogen source, while M. pulcherrima was simply unable to grow under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For the glucose labelling experiment, the SM contained 100 g/L glucose as the sole carbon source and ammonium chloride (300 mg/L YAN) as the nitrogen source. The concentration of organic acids, minerals, and vitamins in the SM were the same as those described by Su et al [ 25 ]. SM was sterilised by filtration through 0.22 μm pore-size membrane filters (Labbox, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrids generated were evaluated and compared to their parental strains in competition experiments to generate phenotypic maps and identify the different recombination events from the expressed phenotypes (García-Ríos et al, 2019a). Wine hybrids were constructed in order to generate strains able to survive and proliferate in low nitrogen levels commonly found in grapes (Su et al, 2019). Nitrogen is essential for yeast metabolism and fermentation ability as it is also responsible for the accumulation of aroma-related compounds (Rollero et al, 2018).…”
Section: Hybridizationmentioning
confidence: 99%
“…In fact, the well-known yeast species S. pastorianus widely studied because of its economic relevance in lager beer fermentations is a hybrid composed by S. cerevisiae and S. eubayanus genome portions that inherited the good fermentation performance from S. cerevisiae and the cold tolerance from S. eubayanus (Baker et al, 2015;Bing et al, 2014;Gibson and Liti 2015;Nakao et al, 2009;Peris et al, 2014Peris et al, , 2016Su et al, 2019). During the last years, many reports have arisen about the generation of artificial hybrids between these two or other yeast species for beer (Hebly et al, 2015;Mertens et al, 2015), wine ( Belloch et al, 2008;García-Ríos et al, 2019;Magalhães et al, 2017a;Su et al, 2019) and cider (Magalhães et al, 2017b) elaboration. In a recent study carried out in our laboratory, two S. uvarum strains selected for their differential oenological characteristics were hybridized with a commercial S. cerevisiae strain, resulting in hybrids with interesting features to be used in the elaboration of Sauvignon Blanc wines in Patagonia (Origone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%